A CROSS-SECTIONAL STUDY ASSESSING THE IMPACT OF ILLEGAL DUMPING OF WASTE MATERIAL BY FISHERMEN AND COMMUNITIES ON RIVERINE BIODIVERSITY IN SELECTED AREAS OF THE EASTERN CAPE PROVINCE, SOUTH AFRICA. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background Illegal dumping of waste by fishermen and surrounding communities has emerged as a serious environmental issue in the Eastern Cape Province of South Africa, with adverse effects on riverine biodiversity. Although pollution is globally acknowledged as a threat to freshwater ecosystems, limited studies have focused specifically on how community-driven illegal dumping affects riverine environments in this region. This study aimed to assess the impact of illegal waste dumping by fishermen and local communities on riverine biodiversity in selected areas of the Eastern Cape. Methodology A cross-sectional mixed-methods design was adopted. Study sites were selected based on high fishing activity and visible waste accumulation. Quantitative data were obtained through biodiversity assessments using established indices, and pollution levels were measured through waste categorization and field observations. Qualitative data were collected through surveys and semi-structured interviews with 45 respondents, including 20 fishermen, 15 community residents, and 10 key stakeholders from local government and environmental organizations. Results The study revealed a significant negative correlation between illegal dumping and riverine biodiversity. Heavily polluted sites (pollution levels between 50%–90%) showed decreased species richness and lower organism abundance. Communities near these sites reported increased sightings of waste-related hazards, such as fish die-offs and foul odours. Socio-economic challenges such as unemployment, poor service delivery, and lack of education were identified as underlying drivers of illegal dumping. Many participants lacked awareness of environmental laws or proper disposal methods, and stakeholders cited weak municipal enforcement and insufficient infrastructure as barriers to effective waste management. Conclusion Illegal dumping poses a serious threat to freshwater biodiversity in the Eastern Cape. Without intervention, ongoing pollution will continue to degrade river ecosystems and threaten aquatic life. Recommendations Improved waste infrastructure, environmental education, and collaborative stakeholder action are urgently needed to curb pollution and support biodiversity conservation.